TrueFISP of the pediatric pineal gland - Bumb, Jan Malte; Brockmann, Marc Alexander; Groden, Christoph; Al-Zghloul, Mansour; Nölte, Ingo (Clinical neuroradiology, 2011)
Purpose: Although high-resolution 3D-imaging has markedly improved the imaging of the pediatric pineal gland, the prevalences of typical and atypical cysts as well as in vivo volumes are unknown.The purpose of this study was to compare the frequency of typical and atypical cysts using high-resolution 3D-sequence true fast imaging with steady state precession (trueFISP) and standard sequences and to directly measure the pineal volume in a large pediatric population.MethodsIn 54 consecutively examined children (age 0-17 years, mean age 5.4 ± 5.6 years, 44% female, 56% male) the prevalence of typical and atypical cysts (thickened rim, trabeculations, asymmetry) was determined using trueFISP (isotropic, 0.8 mm) and standard sequences, 1.5-T, T1-weighted spin echo (T1-SE), T2-weighted turbo spin echo (T2-TSE) and fluid attenuated inversion recovery (FLAIR). Indistinct findings were noted separately. Volumetry was based on the trueFISP datasets. Solid and cystic compartments were approached separately. The pineal volume was correlated to gender and age.Results: The detected frequency of pineal cysts was higher in trueFISP (57.4%) than in standard sequences (T1-SE 7.4%, T2-TSE 14.8%, and FLAIR 13.0%). In trueFISP 66.3% of the detected cysts were classified as atypical (standard sequences 0%). Indistinct findings were lowest in trueFISP. The mean pineal volume was 94.3 ± 159.1 mm³ and no gender related differences were found. Age and volume showed a moderate correlation (r = 0.382) which was remarkably higher in completely solid glands (r = 0.659). Conclusions: TrueFISP imaging improves the detection of pineal cysts in children. A typical cysts are frequently detected as an incidental finding. Volumetric analysis of the pediatric pineal gland is feasible and reveals enormous variation. Whereas gender effects are negligible, the pineal volume in children is dependant on age.